MEMORIAL SPORTS COMPETITIONS: HISTORY, SPECIFICS, PATRIOTIC AND LOCAL HISTORY ASPECTS - Shakhov, A.A.; Semyannikova, V.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the problems of holding memorial and other personal sports competitions in the context of the history and specifics of their conduct, as well as patriotic and local history education of the younger generation. Methods and structure of the study. In the scientific work, an analysis of information sources on the topic under consideration was carried out; analysis of the history of sports in the city of Yelets (mid-19th century - present) in the context of the problem under consideration; generalization of many years of personal experience in holding memorial competitions. Results and conclusions. The conducted studies (on the example of the city of Yelets) made it possible to analyze the historical aspects of holding memorial and other personal sports competitions, to determine the factors associated with their holding. The main components of their educational (local lore and patriotic) resource are revealed: biographical information about the person to whom this event is dedicated; guests of honor; award paraphernalia; laying flowers at a memorial plaque, photograph, portrait, grave of a person to whom the competition is dedicated; the location of the memorial; information support of the memorial